Effect of Drilling Fluid Invasion on Natural Gas Hydrate Near-Well Reservoirs Drilling in a Horizontal Well - Qibing Wang (MDPI AG, 2021)
Horizontal wells can significantly improve the gas production and are expected to be an efficient exploitation method for the industrialization of natural gas hydrates (NGHs) in the future. However, the near-wellbore hydrate is highly prone to decomposition during the drilling process, owing to the disturbance aroused by the factors such as the drilling fluid temperature, pressure, and salinity. These issues can result in the engineering accidents such as bit sticking and wellbore instability, which are required for further investigations. This paper studies the characteristics of drilling fluid invasion into the marine NGH reservoir with varied drilling fluid parameters via numerical simulation. The effects of the drilling fluid parameters on the decomposition behavior of near-wellbore hydrates are presented. The simulating results show that the adjustments of drilling fluid density within the mud safety window have limited effects on the NGH decomposition, meanwhile the hydrates reservoir is most sensitive to the drilling fluid temperature variation. If the drilling fluid temperature grows considerably due to improper control, the range of the hydrates decomposition around the horizontal well tends to expand, which then aggravates wellbore instability. When the drilling fluid salinity varies in the range of 3.5–7.5%, the increase in the ion concentration speeds up the hydrate decomposition, which is adverse to maintaining wellbore stability.